Assessment of Manual Abilities Using the Box and Block Test in Children with Bilateral Cerebral Palsy - Vanessa Zapata-Figueroa; Fernando Ortiz-Corredor (Occupational Therapy International)
Objective. The aim of this study was to determine the correlation between manual dexterity evaluated with the Box and Block Test (BBT) and the performance of daily activities in children with bilateral cerebral palsy (CP). Methods. The BBT was applied to 162 children with cerebral palsy of bilateral distribution aged 6 to 13 years. The level of performance was evaluated according to the Manual Ability Classification System (MACS), Gross Motor Function Classification System (GMFCS), and Pediatric Evaluation of Disability Inventory (PEDI) in the domains of self-care, mobility, and social function. Correlations between the findings of the BBT and the PEDI were determined, and additionally, some specific toileting tasks of the PEDI were evaluated. Results. The results of the BBT were lower in the lowest functional levels of the MACS (p≤0.001). The BBT showed a strong correlation with the domains’ self-care (r=0.8), mobility (r=0.7), and social function (r=0.6) of the PEDI. The BBT was different between children who were able and children who were not able to perform the toileting tasks that were evaluated. A lower capacity in the BBT obtained in children with functional status GMFCS III, IV, and V was associated with poor performance in toileting tasks evaluated in the PEDI. Conclusion. The results of the BBT are correlated with the activities of daily living of children with bilateral CP. The data obtained from this test is used to predict the performance of daily activities of these patients in settings such as school and home and helps to identify contextual factors that influence the level of independence in children with bilateral CP.